Manajemen Pendidikan Islam - Moh. Sholeh (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2018)
Islamic Religious Education with various paths, levels, and forms that exist such as in the formal education path there are basic education levels in the form of Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs), secondary education levels are in the form of Madrasah Alyah (MA) and Madrasah Aliyah Vocational Education (MAK), and at the higher education level there are so many Islamic Religious Universities (PTAI) with various forms, some of which are in the form of academies, Colleges, Institutes, and Universities. In non-formal education channels such as Playgroups, Child Care Parks (TPA), Ta'lim Council, Islamic Boarding Schools and Madrasah Diniyah. Informal education pathways such as education held within the family or education organized by the environment. All of them need management or management as well as possible. Management is a process of utilizing all resources through the help of others and in collaboration with them, so that common goals can be achieved effectively, efficiently, and productively. On the other hand, Islamic education is a process of transinternalizing Islamic values to students as a provision to achieve happiness and prosperity in the world and in the hereafter.